Cocaine perturbs mitovesicle biology in the brain. Issue 1 (24th January 2023) - D'Acunzo, Pasquale; Ungania, Jonathan M.; Kim, Yohan; Barreto, Bryana R.; DeRosa, Steven; Pawlik, Monika; Canals‐Baker, Stefanie; Erdjument‐Bromage, Hediye; Hashim, Audrey; Goulbourne, Chris N.; Neubert, Thomas A.; Saito, Mariko; et al.
Abstract: Cocaine, an addictive psychostimulant, has a broad mechanism of action, including the induction of a wide range of alterations in brain metabolism and mitochondrial homeostasis. Our group recently identified a subpopulation of non‐microvesicular, non‐exosomal extracellular vesicles of mitochondrial origin (mitovesicles) and developed a method to isolate mitovesicles from brain parenchyma. We hypothesised that the generation and secretion of mitovesicles is affected by mitochondrial abnormalities induced by chronic cocaine exposure. Mitovesicles from the brain extracellular space of cocaine‐administered mice were enlarged and more numerous when compared to controls, supporting a model in which mitovesicle biogenesis is enhanced in the presence of mitochondrial alterations. This interrelationship was confirmed in vitro. Moreover, cocaine affected mitovesicle protein composition, causing a functional alteration in mitovesicle ATP production capacity. These data suggest that mitovesicles are previously unidentified players in the biology of cocaine addiction and that target therapies to fine‐tune brain mitovesicle functionality may be beneficial to mitigate the effects of chronic cocaine exposure.